PENGEMBANGAN BAHAN AJAR BROSUR KEARIFAN LOKAL MASYARAKAT TRENGGALEK TRADISI NYADRAN DAM BAGONG UNTUK SISWA KELAS X - Mochammad Nurfahrul Lukmanul Khakim; Marsudi Marsudi; Amalia Firmansyah; Cindy Sintia Dewi; Uskuri Lailal Munna (Jurnal Pendidikan Sejarah Indonesia, 2021)
Nyadran is a living tradition in Trenggalek which is used as a means to show gratitude. However, this important tradition was not incorporated at learning at school. In this research, we aim to develop a brochure to disseminate local knowledge and tradition of Nyadran as supplementary material for history learning at 11th grade. We conducted a literature study to prepare the content of the brochure as teaching material for student in Trenggalek. The content of this brochure related to the arrival of Islam to Trenggalek and the development of Islamic culture in Trenggalek. The compilation of teaching materials in the brochure can be used to enhance students’ knowledge regarding the process of the spread of Islam in Trenggalek and the culture that developed after that.